GEDUNG PERTANIAN HORTIKULTURA MASA DEPAN DI KAMPUNG MUKA - Bryan Wesley; Fermanto Lianto (Jurusan Arsitektur dan Perencanaan, 2021)
Because of the covid-19 virus pandemic in 2020, Indonesia is implementing large-scale social restrictions (PSBB) to protect healthy people from contracting the covid-19 virus. So most residents of Kampung Muka losing their jobs and unable to buy food for their daily needs. So they have to rely on the government’s non-cash food assistance program (BPNT). During the covid-19 pandemic occurred, the residents of Kampung Muka could not survive in their village and had to rely on government assistance to survive. The design method is the everydayness approach, by adding new daily activities in Kampung Muka, namely horticultural agriculture so that the residents can get a new source of livelihood. Also, horticultural agriculture is a source of food for residents during emergencies such as PSBB. Meanwhile, the commercial section is used as a place to sell food products and makes the view of horticultural agriculture a commercial attraction. Keywords: Commercial; Future; Government program; Horticultural agriculture Abstrak Dengan adanya pandemi virus Covid-19 pada tahun 2020, Indonesia memberlakukan pembatasan sosial berskala besar (PSBB) untuk melindungi orang yang sehat agar tidak tertular virus covid-19. Mengakibatkan kebanyakan warga Kampung Muka kehilangan pekerjaannya dan tidak dapat membeli pangan untuk kebutuhan hidup mereka sehari hari. Sehingga mereka harus bergantung pada program bantuan pangan non tunai (BPNT) pemerintah. Pada kondisi yang terjadi saat pandemi covid-19, warga Kampung Muka tidak dapat bertahan hidup di dalam kampung mereka sendiri dan harus bergantung pada bantuan pemerintah untuk bertahan hidup. Metode perancangan yang digunakan adalah pendekatan everydayness, dengan menambah aktivitas keseharian yang baru di Kampung Muka yaitu pertanian hortikultura, agar para warga mendapatkan sumber pencaharian yang baru. Selain itu, pertanian hortikultura juga sebagai sumber pangan para warga saat kondisi darurat seperti PSBB. Sedangkan bagian komersial, dimanfaatkan sebagai tempat untuk menjual hasil pangan dan menjadikan view pertanian hortikultura sebagai daya tarik komersial.